OIL TANKER - Md Yusof, M Aslam (2025)
An oil tanker is a large, specialized ship designed for transporting crude oil or refined petroleum products across oceans and seas. These vessels play a crucial role in the global oil supply chain, moving oil from production sites to refineries and distribution centers. Oil tankers vary in size, from small coastal tankers to massive ultra-large crude carriers (ULCCs), capable of carrying millions of barrels of oil. These vessels play a crucial role in the global energy supply chain by transporting crude oil from oil-producing regions to refineries and then delivering refined products like gasoline, diesel, and jet fuel to various destinations.